Xenopus MAP kinase activator is a serine/threonine/tyrosine kinase activated by threonine phosphorylation. - Kosako, H (1992)
Xenopus MAP kinase activator, a 45 kDa protein, has been shown to function as a direct upstream factor sufficient for full activation and both tyrosine and serine/threonine phosphorylation of inactive MAP kinase. We have now shown by using an anti-MAP kinase activator antiserum that MAP kinase activator is ubiquitous in tissues and is regulated post-translationally. Activation of MAP kinase activator is correlated precisely with its threonine phosphorylation during the oocyte maturation process. It is a key question whether MAP kinase activator is a kinase or not. We have shown that Xenopus MAP kinase activator purified from mature oocytes is capable of undergoing autophosphorylation on serine, threonine and tyrosine residues. Dephosphorylation of purified activator by protein phosphatase 2A treatment inactivates its autophosphorylation activity as well as its activator activity. Thus, Xenopus MAP kinase activator is a protein kinase with specificity for both serine/threonine and tyrosine. Partial protein sequencing of purified activator indicates that it contains a sequence homologous to kinase subdomains VI and VII of two yeast protein kinases, STE7 and byrl.